A New Methodology to Aid Skull–Photograph Superimposition Technique Using Facial Asymmetries in Skull Identification (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
The identification of decomposed head through DNA profiling is considered as conclusive, the identification of the deceased through DNA profiling is not feasible in all the cases because of various reasons. Hence, the investigating agency has to resort to SPS (skull–photograph superimposition) technique for identification purpose. Since there is similarity in facial features of the victims to twins, siblings and close relatives, the SPS technique using ante-mortem face photograph provides only probable opinion on identification. At this juncture, it is inevitable to increase the reliability in skull identification through new methodologies. Many researchers accepted that the asymmetries are the specific characters for skull and face identification. Facial asymmetries are indeed efficient in identifying people. The asymmetry of face is an individual characteristic, differing in perceptible ways even between identical twins. In this study, the correspondence in asymmetry between the skull and face are quantified by a new methodology using the software Adobe Photoshop and AutoCAD. This study establishes the use of symmetries in skull identification and takes SPS technique towards eliminating the subjectivity in skull identification.
Keywords: DNA profiling; Skull–photo superimposition; Asymmetries; Photo shop; AutoCAD